Welfare Effects of Distortionary Tax Incentives under Preference Heterogeneity: An Application to Employer-provided Electric Cars - Alexandros Dimitropoulos; Jos N. van Ommeren; Paul Koster; Piet Rietveld (Tinbergen Institute, 2014)
This paper presents an approach for the estimation of welfare effects of tax policy changes under heterogeneity in consumer preferences. The approach is applied to evaluate the welfare effects of current tax advantages for electric vehicles supplied as fringe benefits by employers. Drawing on stated preferences of Dutch company car drivers, we assess the short-run welfare effects of changes in the taxation of the private use of these vehicles. We find that the welfare gain of a marginal increase in the taxation of electric company cars is substantial and even outweighs the marginal tax revenue raised.
Keywords: D12; H23; H24; H31; O33; Q58; R41; 330; Social welfare; Latent class; Stated preference; Company car; Electric vehicle; Plug-in hybrid